Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2010
DOI: 10.1145/1753326.1753707
|View full text |Cite
|
Sign up to set email alerts
|

How to support designers in getting hold of the immaterial material of software

Abstract: When designing novel GUI controls, interaction designers are challenged by the "immaterial" materiality of the digital domain; they lack tools that effectively support a reflecting conversation with the material of software as they attempt to conceive, refine, and communicate their ideas. To investigate this situation, we conducted two participatory design workshops. In the first workshop, focused on conceiving, we observed that designers want to invent controls by exploring gestures, context, and examples. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 24 publications
(16 reference statements)
0
32
0
Order By: Relevance
“…The five aspects of interaction proposed and focused on in this article can therefore be looked upon as a contribution to the continued work of establishing such a language and to conceptualizing the core issues addressed within the field of interaction design. While the discipline of interaction design is characterized as being a conversation with the immaterial material of software (Ozenc et al 2010), the design students that we have studied do not engage in a conversation with interaction to a great extent but tend to get stuck on material particulars and the appearance of physical representations that they construct. The students in this study did attend to interactivity; e.g., inputting and receiving messages and turn-taking in dialogues between users and an artifact.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The five aspects of interaction proposed and focused on in this article can therefore be looked upon as a contribution to the continued work of establishing such a language and to conceptualizing the core issues addressed within the field of interaction design. While the discipline of interaction design is characterized as being a conversation with the immaterial material of software (Ozenc et al 2010), the design students that we have studied do not engage in a conversation with interaction to a great extent but tend to get stuck on material particulars and the appearance of physical representations that they construct. The students in this study did attend to interactivity; e.g., inputting and receiving messages and turn-taking in dialogues between users and an artifact.…”
Section: Discussionmentioning
confidence: 99%
“…Context of use refers to placing the planned activities or system in specific social and physical contexts which exemplify the artifact in use. (2004) Temporality Buxton (2007), Crampton Smith (2007), Löwgren and Stolterman (2004) Interactivity Löwgren and Stolterman (2004), Silver (2007) Sequentiality Benyon (2010), Löwgren (2002) Context of use Gedenryd (1998), Ozenc et al (2010), Suchman (1987) K. Karlgren et al We account for two groups of students that represent two different examples of how a design task can be approached. By focusing on the use of different materials in representing and re-representing design ideas, taken together with an analysis of how frequently aspects of interaction were addressed, we could observe how the student groups organized their work throughout the design process.…”
Section: Framework For Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The digital systems are dynamically changing as we use them, they respond to the user's request or request information from the user, they work in several temporal dimensions, and the design imposes some structural order on how the user might use the artifact. The tasks or the context where we use the computer system also affect, or define, the system (Gedenryd, 1998;Ozenc, Kim, Zimmerman, Oney, & Myers, 2010). These aspects of interaction are all of importance when designing interactive systems.…”
Section: A I Mmentioning
confidence: 99%
“…[1]. Although a number of surveys and empirical evidence have shown that designers need better tools to manage and evaluate these design artifacts [1][2] [3], designers are still using ad-hoc versioning solutions, like manually renaming files [1] [4].…”
Section: Introductionmentioning
confidence: 99%